Ligand‐Conformer‐Induced Formation of Zirconium–Organic Framework for Methane Storage and MTO Product Separation - Fang, Han; Zheng, Bin; Zhang, Zong‐Hui; Li, Hong‐Xin; Xue, Dong‐Xu; Bai, Junfeng (Angewandte Chemie International Edition, 2021)
In pursuit of novel adsorbents with efficient adsorptive gas storage and separation capabilities remains highly desired and challenging. Although the documented zirconium‐tricarboxylate‐based metal–organic frameworks (MOFs) have displayed a variety of topologies encompassing underlying and geometry mismatch ones, the employed organic linkers are exclusively rigid and poorly presenting one type of conformation in the resultant structures. Herein, a used and semirigid tricarboxylate ligand of H3TATAB was judiciously selected to isolate a zirconium‐based spe‐MOF after the preliminary discovery of srl‐MOF. Single‐crystal X‐ray diffraction reveals that the fully deprotonated TATAB linker in spe‐MOF exhibits two distinct conformers, concomitant with popular Oh and rare S6 symmetrical Zr6 molecular building blocks, generating an unprecedented (3,3,12,12)‐c nondefault topology. Specifically, the spe‐MOF exhibits structurally higher complexity, hierarchical micropores, open metal sites free and rich electronegative groups on the pore surfaces, leading to relatively high methane storage capacity without considering the missing‐linker defects and efficient MTO product separation performance. One topologically unprecedented zirconium–organic framework was successfully assembled by virtue of a used and semirigid tricarboxylate ligand via ligand‐conformer‐induction. The spe‐MOF exhibits relatively high methane storage capacity and efficient MTO product separation performance due to its integrated features, shedding light on the development of novel zirconium‐based adsorbents by the utilization of semirigid organic linkers aiming advanced applications.